Introduction To Linear Optimization - Nemirovski, Arkadi (Singapore : World Scientific, 2024)
The book presents a graduate level, rigorous, and self-contained introduction to linear optimization (LO), the presented topics being expressive abilities of LO; geometry of LO $1 (Bstructure of polyhedral sets, LO duality and its applications; traditional LO algorithms $1 (Bprimal and dual simplex methods, and network simplex method; polynomial time solvability of LO via ellipsoid algorithm; conic programming with emphasis on expressing abilities of second order and semidefinite optimization, and polynomial time primal-dual interior point algorithms for linear and semidefinite optimization.s
Includes appendix,bibliography and index.
Keywords: Linear programming; Algorithms; Conic programming; Ellipsoid method